Replication of Legionella Pneumophila in Human Cells: Why are We Susceptible? - Abu Khweek, Arwa; Amer, Amal (Frontiers in Microbiology, 2010)
Legionella pneumophila is the causative agent of Legionnaires’ disease, a serious and often fatal form of pneumonia. The susceptibility to L. pneumophila arises from the ability of this intracellular pathogen to multiply in human alveolar macrophages and monocytes. L. pneumophila also replicates in several professional and non-professional phagocytic human-derived cell lines. With the exception of the A/J mouse strain, most mice strains are restrictive, thus they do not support L. pneumophila replication. Mice lacking the NOD-like receptor Nlrc4 or caspase-1 are also susceptible to L. pneumophila. On the other hand, in the susceptible human hosts, L. pneumophila utilizes several strategies to ensure intracellular replication and protect itself against the host immune system. Most of these strategies converge to prevent the fusion of the L. pneumophila phagosome with the lysosome, inhibiting host cell apoptosis, activating survival pathways, and sequestering essential nutrients for replication and pathogenesis. In this review, we summarize survival mechanisms employed by L. pneumophila to maintain its replication in human cells. In addition, we highlight different human-derived cell lines that support the multiplication of this intracellular bacterium. Therefore, these in vitro models can be applicable and are reproducible when investigating L. pneumophila/phagocyte interactions at the molecular and cellular levels in the human host.